2018
DOI: 10.4236/ce.2018.99101
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Plasticity of Boldo Mirim (<i>Plectranthus neochilus</i> Schlechter) within Rach of Children from Second Degree of Elementary School

Abstract: Is it possible to promote the construction of knowledge about phenotypic plasticity expressed by plants among elementary school students?" To answer this question, it was proposed to carry out experiments together with second year students of elementary school using the plant popularly known as Boldo Mirim (Plectranthus neochilus Schlechter). The objective of present study was to describe the results of the experiment performed on cuttings of Boldo Mirim raised in two types of soil [plant compost + poultry man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
2
5
0
6
Order By: Relevance
“…The growth patterns of Boldo Brasileiro corroborated with the results obtained by other studies that involved Boldo Mirim (Rosal et al, 2011;Lima, 2017;Sodré et al, 2018;Lima, 2019;Sodré et al, 2019). Thus, the experiments developed in the present study can be reproduced in other schools to approach aspects of environmental importance through the expression of phenotypic plasticity expressed by plants in response to environmental variables.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The growth patterns of Boldo Brasileiro corroborated with the results obtained by other studies that involved Boldo Mirim (Rosal et al, 2011;Lima, 2017;Sodré et al, 2018;Lima, 2019;Sodré et al, 2019). Thus, the experiments developed in the present study can be reproduced in other schools to approach aspects of environmental importance through the expression of phenotypic plasticity expressed by plants in response to environmental variables.…”
Section: Discussionsupporting
confidence: 89%
“…Analyzes of soil composition revealed that the compound of earthworm humus + bovine manure presented a double of the percentage of carbon when compared to the soil containing plant compounds and poultry manure. As expected, these results confirm that soil type 1 contained more micronutrients than soil type 2, as observed by Sodré et al (2018).…”
Section: Analyses Of Soilssupporting
confidence: 90%
See 3 more Smart Citations